Does an analysis of polychlorinated biphenyl (PCB) distribution in mountain soils across China reveal a latitudinal fractionation paradox? - Zheng, Qian; Nizzetto, Luca; Mulder, Marie D; Sáňka, Ondřej; Lammel, Gerhard; Li, Jun; Bing, Haijian; Liu, Xin; Jiang, Yishan; Luo, Chunlin; Zhang, Gan (Environmental pollution (Barking, Essex, 2014)
Organic and mineral soil horizons from forests in 30 mountains across China were analysed for polychlorinated biphenyl (PCB). Soil total organic carbon (TOC) content was a key determinant of PCB distribution explaining over 90% of the differences between organic and mineral soils, and between 30% and 60% of the variance along altitudinal and regional transects. The residual variance (after normalization by TOC) was small. Tri- to tetra-CB levels were higher in the South in relation to high source density and precipitation. Heavier congeners were instead more abundant at mid/high-latitudes where the advection pattern was mainly from long range transport. This resulted in a latitudinal fractionation opposite to theoretical expectations. The study showed that exposure to sources with different characteristics, and possibly accumulation/degradation trends of different congeners in soils being out-of-phase at different latitudes, can lead to an unsteady large scale distribution scenario conflicting with the thermodynamic equilibrium perception.
Keywords: Latitude; polychlorované bifenyly; Forest; Čína; Chemical Fractionation; Environmental Monitoring; Soil Pollutants; látky znečišťující půdu; Cold trapping; půda; China; Mountain; PCB; monitorování životního prostředí; Fractionation; Soil; chemická frakcionace; Polychlorinated Biphenyls; POP